2022
DOI: 10.3892/mmr.2022.12680
|View full text |Cite
|
Sign up to set email alerts
|

KLF4 downregulates FGF21 to activate inflammatory injury and oxidative stress of LPS‑induced ATDC5 cells via SIRT1/NF‑κB/p53 signaling

Abstract: Ankylosing spondylitis (AS) is a chronic inflammatory disease. Transcriptional regulation of fibroblast growth factor 21 (FGF21) by the transcription factor Krüppel-like factor 4 (KLF4) serves an important role in chronic inflammatory disease. However, to the best of our knowledge, the role of both these factors in AS has not been previously reported. In the present study, ATDC5 cells were induced by lipopolysaccharide (LPS) to establish an AS inflammatory injury model. The expression levels of FGF21 and KLF4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…The subsequent rescue experiment revealed that KLF4 overexpression facilitated inflammation and pyroptosis of AP acinar cells. In line with our data, KLF4 upregulation increased the levels of oxidative stress markers and proinflammatory cytokines in LPS-treated ATDC5 cells in ankylosing spondylitis (52), and KLF4 deficiency imparts an anti-inflammation role in dextran sodium sulfate–triggered colitis (53). Moreover, decreased KLF4 expression diminishes pyroptosis of Ang-II–treated vascular smooth muscle cells by blocking the PI3K/AKT signaling pathway (54).…”
Section: Discussionsupporting
confidence: 90%
“…The subsequent rescue experiment revealed that KLF4 overexpression facilitated inflammation and pyroptosis of AP acinar cells. In line with our data, KLF4 upregulation increased the levels of oxidative stress markers and proinflammatory cytokines in LPS-treated ATDC5 cells in ankylosing spondylitis (52), and KLF4 deficiency imparts an anti-inflammation role in dextran sodium sulfate–triggered colitis (53). Moreover, decreased KLF4 expression diminishes pyroptosis of Ang-II–treated vascular smooth muscle cells by blocking the PI3K/AKT signaling pathway (54).…”
Section: Discussionsupporting
confidence: 90%
“…The results of the GO enrichment analysis showed that biological processes were mainly related to the relevance of organismal responses, such as the response to oxidative stress, lipopolysaccharides, and reactive oxygen species. A recent in vitro study on ankylosing spondylitis found that KLF4 downregulates FGF21 via the SIRT1/NF- κ B/p53 signaling pathway to activate LPS-induced inflammatory damage and oxidative stress in ATDC5 cells [ 50 ]. There was also evidence that excessive inflammatory responses and oxidative stress are thought to be the main features of inflammatory bowel disease [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…KLF4 transactivated the cyclin-dependent kinase inhibitor 1A (CDKN1A) promoter, where CDKN1A is involved in cell apoptosis and upregulated in the hippocampus of anxious mice [ 48 , 49 ]. Through SIRT1/NF-κB/p53 signaling, KLF4 activates inflammatory injury and oxidative stress in LPS-induced ATDC5 (chondrogenic cell line) cells [ 50 ]. Studies on inflammation and oxidative stress have shown that KLF4 may cause anxiety through changes in the physiology of the brain [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%